2005
DOI: 10.1002/syn.20174
|View full text |Cite
|
Sign up to set email alerts
|

A transient expression of functional α2-adrenergic receptors in white matter of the developing brain

Abstract: Norepinephrine is a neurotransmitter with peripheral and central actions mediated by alpha-1, alpha-2, and beta-adrenergic receptors. In this paper, we report an expression of alpha-2 adrenergic receptors in developing white matter tracts as revealed by [(3)H]RX821002 autoradiography. In rats, these receptors are present in the corpus callosum and anterior commissure at gestational day 20. Quantification of their postnatal expression reveals peak expression in the corpus callosum at postnatal day 1, which decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…This contrast from the adult response is consistent with many studies showing that the neonatal noradrenergic system is very different from the mature state [5, 7-9, 29]. In the neonatal brain, the α 2 -AR and IEGs are differentially expressed and regulated by norepinephrine compared to the adult brain [5, 6, 9]. The developmental response to specific adrenergic receptor agonists also differs in the neonate compared to the adult.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This contrast from the adult response is consistent with many studies showing that the neonatal noradrenergic system is very different from the mature state [5, 7-9, 29]. In the neonatal brain, the α 2 -AR and IEGs are differentially expressed and regulated by norepinephrine compared to the adult brain [5, 6, 9]. The developmental response to specific adrenergic receptor agonists also differs in the neonate compared to the adult.…”
Section: Discussionsupporting
confidence: 88%
“…Further research has indicated that norepinephrine may be critical for guiding the development of specific brain regions. Noradrenergic receptors and transporters, for instance, are enriched in many specific brain areas during times of early brain development and dramatically decrease in expression with maturity, suggesting important developmental roles [5, 6]. More recently, the noradrenergic system has been characterized by differences in its regulation of the developing versus mature brain [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…Functional white matter  and 1 adrenoreceptors have also been described (Sanders et al, 2005;Venugopalan et al, 2006;Nikolaeva et al, 2009;Honmou & Young, 1995), and 2 receptor protein is expressed in white matter astrocytes (Nikolaeva et al, 2009). 1 receptor activation can affect axon excitability in neonatal white matter but not adult, consistent with the transient 1 mRNA expression found here.…”
Section: Figure 3 Near Heresupporting
confidence: 83%
“…A role for A2AR during development is suggested by early mRNA expression and protein enrichment in developing brain (Happe et al, 2004; Lidow and Rakic, 1994; Sanders et al, 2005b; Winzer-Serhan and Leslie, 1997; Winzer-Serhan et al, 1997a; Winzer-Serhan et al, 1997b). Behavioral studies with transgenic A2AR animals also support a role for these receptors in the development and final expression of important CNS functions.…”
Section: Discussionmentioning
confidence: 99%
“…In areas such as the basal ganglia, amygdala, thalamus, spinal cord and brainstem A2AR-A mRNA is expressed at high levels in early development and then decreases with subsequent maturation of the nervous system (Winzer-Serhan et al, 1997a). A2AR are expressed at very high levels in white matter of developing rat CNS, then disappear in adulthood, indicating a role in regulating development (Sanders et al, 2005b). In cortex of the embryonic rhesus monkey A2AR display a high receptor density which surpasses that for most other receptors (Lidow and Rakic, 1994).…”
mentioning
confidence: 99%